Rancang Bangun Perpustakaan Berbasis Website di SMAN 21 Bandung sebagai upaya untuk Mengurangi Biaya Pengadaan Koleksi - Aminudin; Agustine, Merryam; Rejeki, Diah Sri; Abinowi, Egi; Wahyuni, Haria Saputry (Jurnal Informatika Ekonomi Bisnis, 2024)
The school library is one of the places of learning in schools to assist students in finding and adding knowledge. With the advancement of information technology, school libraries have shifted from conventional libraries to digital libraries. Digital libraries have advantages over conventional libraries because websites can be accessed anywhere and no longer need to come to the library. Thus the current digital library is very much needed. The purpose of this research is to design a website-based digital library at SMAN 21 Bandung, this is because SMAN 21 Bandung has a conventional library. The method used in this research is descriptive qualitative research method, while the data collection techniques are carried out by conducting observations, interviews and literature studies. The result of this research is to produce a web - based digital library design at SMAN 21 Bandung. This research produces a digital library design consisting of User Login Features, User Authority, New Member Input, Collection Input, Collection Borrowing, Collection Returns, Borrowing and Returning Reports, Forums. For future research, it is possible to apply digital attendance and labeling of collections using RFID so that it can facilitate daily operations in the library.